FRAGMENTASI SPASIAL PENGGUNAAN LAHAN MENGGUNAKAN SPATIAL METRIC DI KECAMATAN MAPANGET DAN BUNAKEN KOTA MANADO - Sela, Rieneke; Malik, Andy; Tilaar, Sony; Mambu, Dwight; Pelealu, Rodrygo Hendry (JAMBURA Journal of Architecture, 2025)
ABSTRACT. Changes in land use and possible deviations as well as the presence of Manado City RTRW 2024â€“2042 are new spatial aspects of the strategic area of the city need to be studied further to support development planning. The aim of this study is to look at land use changes in 2014â€“2024 in Mapanget and Bunaken districts, which are strategic areas in Manado City. This study uses a spatial metric method, which is used to see the spatial fragmentation of how many areas of land are divided into smaller and separated parts. Variables used are NP, Patch Density, and SHDI . The outcome in the Mapanget district showed an increase in the value of NP and PD on housing land, indicating that the use of housing lands was increasingly spread from 2014 - 2024. On the other hand, in Bunaken district, NP values and PD increased on Settlements, Bushes and Road. SHDI in Mapanget district indicates a small increase in value and Bunaken district has a decrease, it indicates that the small level of development of land use in Mapanget and Bunaken districts..  Keywords: Fragmentasi spasial, Land use, Spatial Metric